PENGARUH LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Faradhita Fitriana Nurul Fajri, 13.05.52.0136; Srimindari, Ceacilia (Students' Journal of Accounting and Banking, 2017)
This study examines the effect of liquidity and the size of the company on the capital structure to profitability as a moderating variable. This research was conducted at the Indonesian Stock Exchange by using analysis unit property and real estate that have gone public. The sampling method using purposive sampling the study period of 2013 to 2015. The relationship and influence between variables or described by using multiple regression analysis. The results showed that the size of the company's liquidity and significant positive effect on the capital structure. Moderating testing proves that profitability is not proven as moderating variable that can strengthen or weaken and moderate the relationship sized companies on capital structure. While testing the moderating profitability proved to be a moderating variable that can strengthen or weaken and moderate the relationship of liquidity to capital structure on property and real estate companies listed on the Stock Exchange for the period 2013-2015.Keywords: Liquidity, Company Size, Profitability, and Capital Structure